STUDENTS’ ENGAGEMENT IN SPEAKING CLASS TAUGHT BY USING ENGLISH SONG: THE STUDY OF ISLAMIC ELEMENTARY SCHOOL IN KUDUS - Latifaturrizqia, Ummi; Kurniati, Diah; Rokhayani, Atik (SIMPLE: International Journal of English Education, 2023)
The researchers found problems with the focus abilities of Students at one of the Islamic elementary school in Kudus, they often did not listen to lessons which made them lack vocabulary and have difficulty speaking English. The purpose of this study was to find out how English songs affect the speaking ability of third-grade Islamic elementary school students. The design of the research is qualitative research with the third-grade students of the Islamic elementary school in Kudus as a participant. The instrument of this research is an observation checklist which is adapted from the International Center for Leadership in Education (ICLE) with consists of five aspects that are related to learner engagement, each aspect consists of several Likert-type format statements which required a numerical scale varying from 1 through 4, namely (1) is a rating of low, (2) medium, (3) good, and (4) very good. The results of the research are the use of songs as a medium for teaching children to speak English is effective.